Oral health assessment in Senegal: stepwise method. (30th September 2020) - Kanouté, A; Diop, M; Dieng, S; Mbow, S; Niang, S; Gaye, A; Cisse, M K; Faye, D
Abstract: Background: The STEPwise approach to surveillance (STEPS) helps to assess the prevalence and risk factors of major chronic diseases. Designed to have the ability to integrate optional modules, it allows any attitude to collect data according to planning, prevention and advocacy strategies for the allocation of resources of member countries. The Ministry of Health of Senegal took the option in 2015 to include the oral health module in the STEPS program. This original public health approach has necessitated the development of specific methods and tools that are presented in this communication. Methodology: On the initiative of the WHO Regional Office for Africa and the Ministry of Health of Senegal, behavioral, clinical and biological modules have been validated to identify risk factors and the prevalence of dental and periodontal diseases. Integrated into the Stepwise National Observational Transversal Study, including 6306 adults aged 18-69, these modules provide a framework for future studies. The evaluation of the program, via a SWOT analysis, formalizes the positive and negative points and identifies the factors of its environment that may favorably or negatively influence the recommendations. Results: 62.5% of subjects had never used oral care. The prevalence of caries was 76.3% with an average DMF of 5.5. Strong institutional political will to promote oral health as well as good intra sectoral collaboration emerge. However, the economic constraints remain for a sustainability as well as a limit in the harmonization and the political valorization of the data in terms of recommendations of strategies of health. Conclusions: Integrating oral health into the Stepwise survey provides national information in a context of scarcity of resources. Obtaining integrated quality data should allow for a standardized extension of the program to other countries in the Africa region, subject to adjustments and corrective measures. Key messages: Integrating oral health into the Stepwise survey provides national information in a context of scarcity of resources. Obtaining integrated quality data should allow for a standardized extension of the program to other countries in the Africa region.